Protocol for developing a healthcare transition intervention for young people with spinal cord injuries using a participatory action research approach. Issue 7 (29th July 2021) - Bray, Emily Alice; George, Ajesh; Everett, Bronwyn; Salamonson, Yenna; Ramjan, Lucie
Abstract : Introduction: While healthcare transition (HCT) interventions are recognised as an important area in paediatric rehabilitation, there has been limited research focusing on young people with spinal cord injuries (SCI). In this study, researchers will collaborate with young people with SCI and their parents/caregivers to develop, implement and evaluate the feasibility and acceptability of a HCT intervention aimed at supporting young people with SCI during their transition from paediatric to adult healthcare services. Methods and analysis: A participatory action research (PAR) approach will be used to co-develop the HCT intervention with young people with SCI aged 14–25 years and their parents/caregivers. Three phases will be conducted to address the five objectives of this study. Phase 1 will use semi-structured interviews to explore young people and parent/caregivers' experiences of HCT. In Phase 2a, both young people and parent/caregivers will be co-researchers. They will be included in the analysis of the interviews and will be asked to participate in co-design workshops to inform the development of a prototype HCT intervention. In Phase 2b, using focus groups, feedback on the prototype HCT intervention will be collected. In Phase 3, the refined prototype HCT intervention will be implemented, and young people with SCI and parent/caregivers will evaluate the feasibility and acceptability of the HCT intervention in semi-structured interviews. A reference group, including stakeholders and end users, will be consulted at different time points. Ethics and dissemination: The study has received ethics approval from Western Sydney University Human Research and Ethics Committee (H14029). The researcher will use the results of this study as chapters in a thesis to obtain a Doctor of Philosophy degree. The findings will be disseminated via publication in peer-reviewed journals and will be presented at local, national or international conferences. Trial registration number: ACTRN12621000500853